Was Robert Gibrat Right? A Test Based on the Graphical Model Methodology - Marco Guerzoni; Luigi Riso; Marco Vivarelli (Institute of Labor Economics (IZA), 2023)
Using both regression analysis and an unsupervised graphical model approach (never applied before to this issue), we confirm the rejection of the Gibrat's law when our firm-level data are considered over the entire investigated period, while the opposite is true when we allow for market selection. Indeed, the growth behavior of the re-shaped (smaller) population of the survived most efficient firms is in line with the Law of Proportionate Effect; this evidence reconciles early and current literature testing Gibrat's law and may have interesting implications in terms of both applied and theoretical research.
Keywords: L11; 330; Gibrat's Law; firm survival; market selection; firm growth